The reciprocal relationship between compounding awareness and vocabulary knowledge in Chinese: a latent growth model study - Cheng, Yahua; Li, Liping; Wu, Xinchun (Frontiers in Psychology, 2015)
The aim of this study is to examine the developmental relationship between compounding awareness and vocabulary knowledge from grades 1 to 2 in Chinese children. In this study, 149 Chinese children were tested on compounding awareness and vocabulary knowledge from Time 1 to Time 4, with nonverbal IQ, working memory, phonological awareness, orthographical awareness, and rapid automatized naming at Time 1 as control variables. Latent growth modeling was conducted to analyze the data. Univariate models separately calculated children’s initial levels and growth rates in compounding awareness and vocabulary knowledge. Bivariate model was used to examine the direction of the developmental relationships between the two variables with other cognitive and linguistic variables and the autoregression controlled. The results demonstrated that the initial level of compounding awareness predicted the growth rate of vocabulary knowledge, and the reverse relation was also found, after controlling for other cognitive and linguistic variables and the autoregression. The results suggested a reciprocal developmental relationship between children’s compounding awareness and vocabulary knowledge for Chinese children, a finding that informs current models of the relationship between morphological awareness and vocabulary knowledge.